Philosophical Mudejarism: the Critique of the Creation and the Prophetology in the "Visión Deleytable" - Rivera García, Antonio (Anales del Seminario de Historia de la Filosofía, 2018)
The paper shows how relevant the relationship (and strain) between theoria and the Holy Scriptures is in order to understand Alfonso de la Torre’s Visión Deleytable. The criticism of the Creation by the allegorical character “Entendimiento” (“Insight” or “Understanding”) agrees with the tradition of the unbelieving “Marrano” (converted Jew) Averroism that culminates in XVIIth century Holland, since de la Torre comes across as a philosopher who dispenses with the knowledge revealed by the Scriptures. On the other hand, the objections by “Insight” concur with a philosophy that aims to harmonize reason (theoria) and Holy Writ (faith), as in the case of Maimonides. This harmonization turns out perfect in the Prophet because he is inspired by the active intellect. Due to the decisive influence of Muslim and Jewish prophetology on Alfonso de la Torre’s work, we state that this text is a very relevant example of philosophical Mudejarism.